Niewidzenie a kompetencje pragmatyczne w komunikacji - Czerwińska, Kornelia; Piskorska, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The paper argues that gaps in knowledge attested in congenitally blind individuals may negatively affect their performance in foreign language tasks testing reading comprehension. Characteristics of a blind learner at various stages of cognitive and educational development are presented, with focus on gaps in knowledge resulting from sight impairment. The concept of pragmatic competence is first explained generally in reference to communication and then it is applied to a case of a comprehension task taken from an EFL exam (Polish “matura”, basic level). An analysis of the text indicates that despite being relatively simple in linguistic terms, comprehension tasks may pose a significant processing challenge to blind students due to a large amount of implicitly communicated information dependent on visual experience.